Approaches to the organization of workplaces in "open space" offices - Hofreiter, Ladislav; Ilinska, Olha (Національний технічний університет "Харківський політехнічний інститут", 2019)
The aspects that should be considered when organizing workplaces in "open space" type offices are considered.

Розглянуто аспекти, які доцільно враховувати при організації робочіх місць в офісах типу "open space".
Підходи до організації робочих місць в офісах типу "open space"
Keywords: ergonomics; working conditions; open space office; ергономіка; умови праці; офіс типу "Open space"